A Project Report on Partial Replacement of Coarse Aggregate by Overburnt Bricks in Concrete - Mohamed, A. Marzooq; Manikandan, S.; Shakil, H.; Janani, T. (European Journal of Life Safety and Stability (2660-9630), 2023)
The use of concrete as a building material is widespread throughout the globe. Water, sand, cement, and rock aggregates are the standard ingredients in concrete. The coarse aggregate used in this project describes larger pieces of concrete. The coarse aggregate of rock normally used in concrete will be swapped out for the other ingredient. Overcooked bricks are included in this category. Because of its accessibility, this item was selected. The brick factory is where you can get your hands on some burned bricks. Many bricks are also rejected throughout the brickmaking process because they do not meet the necessary standards. The inconsistent temperature regulation in the kiln results in distorted brick form, a major non-conformity. These discarded bricks can be used as coarse aggregate as well. This would not only put the material to good use, but it would also help solve disposal issues. Partial replacement of the burnt brick bat with coarse aggregate was employed to test the concrete’s mechanical qualities.